2001
DOI: 10.1159/000050857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Vitamin E on Keratocyte Apoptosis after Traditional Photorefractive Keratectomy

Abstract: Purpose: To evaluate the keratocyte apoptosis and effects of topical vitamin E on keratocyte apoptosis after photorefractive surgery. Methods: Rabbits were divided into 7 groups, and all groups were compared with controls after epithelial scraping, epithelial scrape and photorefractive keratectomy (PRK) (traditional PRK), transepithelial PRK, production of a corneal flap with microkeratome and laser-assisted in situ keratomileusis (LASIK). The effects of topical Vitamin E treatment were investigated in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…22 The preventive effect of topical vitamin E on keratocyte apoptosis after PRK has been demonstrated and it is suggested that free radicals might be partly responsible for keratocyte apoptosis after excimer laser keratectomy. 23 …”
Section: Discussionmentioning
confidence: 99%
“…22 The preventive effect of topical vitamin E on keratocyte apoptosis after PRK has been demonstrated and it is suggested that free radicals might be partly responsible for keratocyte apoptosis after excimer laser keratectomy. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The main treatment goal in patients with keratoconus was to increase corneal thickness in preparation for reshaping with refractive surgery and to replace diseased Bowman's membrane and anterior stroma with healthy tissue. In patients with post-LASIK ectasia, the surgical aim was to increase corneal thickness, ablate apoptotic cells in the interface, 18,19 and reduce posterior corneal steepness with tight suturing of the thicker donor lamellae. The goal in the corneal stromal opacity group was to remove diseased stroma and replace it with healthy donor stroma while preserving the host endothelium.…”
Section: Methodsmentioning
confidence: 99%
“…Transepithelial photorefractive keratectomy (PRK) was performed to remove diseased Bowman' s membrane and anterior stroma and to prevent new keratocyte apoptosis. [18][19][20][21] The corneal button and interface were irrigated vigorously with a balanced salt solution. Both the button and interface were dried with fiber-free sponges to remove all debris and maintain the button' s central position by increasing adhesion of the button to the interface.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Vitamin A is thought to be an essential factor for normal epithelial cell growth, and its deficiency can result in xerosis of the ocular surface and other organs [27,34]. Vitamin A downregulates the number of EGF receptors of the conjunctival epithelium, thus promoting differentiation of conjunctival cells [42], and vitamin E can prevent keratocyte apoptosis [3].…”
Section: The Epitheliotrophic Factors In Serum Eyedropsmentioning
confidence: 99%